Evaluation of cost-utility in middle ear implantation in the 'Nordic School': a multicenter study in Sweden and Norway. (January 2014) - Edfeldt, Lennart; Strömbäck, Karin; Grendin, Joakim; Bunne, Marie; Harder, Henrik; Peebo, Markus; Eeg-Olofsson, Måns; Petersson, Carl-Magnus; Konradsson, Konrad
Abstract Conclusion: Hearing restoration using an active middle ear implant (AMEI) is a highly cost-effective treatment for a selected group of patients with no other possibilities for auditory rehabilitation. Objectives: To evaluate the cost-utility of using an AMEI for hearing rehabilitation. Methods: This was a prospective, multicenter, single-subject repeated study in six tertiary referral centers. Twenty-four patients with sensorineural (SNHL), conductive (CHL), and mixed hearing loss (MHL) were implanted with the AMEI Vibrant Soundbridge® (VSB) for medical reasons. All patients were previously rehabilitated with conventional hearing aids. Multiple validated quality of life patient questionnaires, Health Utilities Index (HUI 2 and 3), and Glasgow Hearing Aid Benefit Profile (GHABP) were used to determine the utility gain and quality adjusted life years (QALY). Directly related treatment costs for the implantation were calculated and related to utility gain and QALY. Results: The cost/QALY for patients with SNHL was estimated at €7260/QALY, and for patients with C/MHL at €12 503/QALY.